Enhanced electromagnetic microwave absorption of SiOC ceramics targeting the integration of structure and function. Issue 13 (October 2021) - Feng, Yurun; Guo, Xue; Huang, Kai; Elsayed, Hamada; Franchin, Giorgia; Gong, Hongyu; Colombo, Paolo
Abstract: The electromagnetic waves (EMW) absorption properties of SiOC ceramics synthesized by polymer-derived method were investigated, and additive manufacturing was employed to obtain the integration of structure and functions. The presence of free carbon and β-SiC nanocrystallites increased the internal relaxation interfacial polarization, which improved the EMW absorption properties significantly. In particular for the sample pyrolyzed at 1200 °C, the effective absorption bandwidth (EAB, RL<-10 dB) and minimum reflection loss (RL)were 4.9 GHz (at a thickness of 1.58 mm) and -23.5 dB, respectively, indicating the excellent EMW absorption properties of this SiOC material. In addition, we 3D printed two typical porous structures (a log-pile grid and a gyroid) in which the thickness of solid element corresponded to the one providing optimal absorption. Additive Manufacturing of designed structures will enable to improve and further optimize the selection and control of the absorbing material in practical applications.